2012
DOI: 10.1016/j.jfma.2012.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Use of an intubating laryngeal mask airway on out-of-hospital cardiac arrest patients in a developing emergency medical service system

Abstract: Well-trained EMTs were able to insert the ILMA and ventilate OHCA patients properly in prehospital settings, and ILMA-treated OHCA patients had better short-term outcomes than BVM-treated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Although the authors declare no significant difference in demographic data, the BVM group had a higher incidence of traumatic arrest (21.3% vs. 14.2%), and two key chronic co-morbidities (cerebrovascular 13.5% vs. 4.2%, and diabetes 28.1% vs. 16.9%) (27). The feasibility study from Austria (26) was similar to the feasibility Taiwanese study (27), looking at introducing the LT to their EMS system (26). The methods of this study indicate that the LT would be the primary airway device used in an OHCA, without any prior BVM ventilation, and also if the LT had two failed insertion attempts then BVM would be used instead.…”
Section: Comparison Of Sad and Bvm Studiesmentioning
confidence: 89%
See 3 more Smart Citations
“…Although the authors declare no significant difference in demographic data, the BVM group had a higher incidence of traumatic arrest (21.3% vs. 14.2%), and two key chronic co-morbidities (cerebrovascular 13.5% vs. 4.2%, and diabetes 28.1% vs. 16.9%) (27). The feasibility study from Austria (26) was similar to the feasibility Taiwanese study (27), looking at introducing the LT to their EMS system (26). The methods of this study indicate that the LT would be the primary airway device used in an OHCA, without any prior BVM ventilation, and also if the LT had two failed insertion attempts then BVM would be used instead.…”
Section: Comparison Of Sad and Bvm Studiesmentioning
confidence: 89%
“…The results for the patient outcomes section are conflicting, and report associations that are not congruent with the wellknown airway management gold standard of ETI, with two large studies reporting more favourable patient outcomes for BVM in comparison to ETI (1,2). In comparison between SADs and BVM, three studies report that BVM ventilation was associated with greater patient outcomes (1,2,5), one study reported favourable patient outcomes were similar between advanced airway and BVM ventilation (28), and two studies reported higher successful ventilation and 24 hour survival rates of SADs over BVM (26,27). The majority of patient outcome focussed studies with large sample sizes originate from Japan or the USA, and to a lesser extent, Korea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, tracheal intubation leads to laryngeal edema, airway injury, and other complications. Hence, clinicians do not support tracheal intubation due to concerns over its safety and effectiveness [1].…”
Section: Introductionmentioning
confidence: 99%